Highly pathogenic avian influenza virus subtype H5N1 in Mute swans in the Czech Republic - Nagy, Alexander; Machová, Jiřina; Horníčková, Jitka; Tomči, Miroslav; Nágl, Ivan; Horyna, Bedřich; Holko, Ivan (Veterinary microbiology, 2007)
In order to determine the actual prevalence of avian influenza viruses (AIV) in wild birds in the Czech Republic extensive surveillance was carried out between January and April 2006. A total of 2101 samples representing 61 bird species were examined for the presence of influenza A by using PCR, sequencing and cultivation on chicken embryos. AIV subtype H5N1 was detected in 12 Mute swans (Cygnus olor). The viruses were determined as HPAI (highly pathogenic avian influenza) and the hemagglutinin sequence was closely similar to A/mallard/Italy/835/06 and A/turkey/Turkey/1194/05. Following the first H5N1 case, about 300 wild birds representing 33 species were collected from the outbreak region and tested for the presence of AIV without any positive result. This is the first report of highly pathogenic avian influenza subtype H5N1 in the Czech Republic. The potential role of swan as an effective vector of avian influenza virus is also discussed.
Keywords: Chick Embryo; Animals; Prevalence; divoká zvířata; Molecular Sequence Data; ptačí chřipka u ptáků; surveillance populace; Influenza A Virus, H5N1 Subtype; Phylogeny; prevalence; molekulární sekvence - údaje; Animals, Wild; Czech Republic; Population Surveillance; virus chřipky A, podtyp H5N1; Influenza in Birds; Česká republika; zvířata; fylogeneze; Anseriformes; kuřecí embryo